Dams in the Amazon: The importance of maintaining free‐flowing tributaries for fish reproduction. Issue 5 (15th September 2020) - Vasconcelos, Lilian Paula; Alves, Diego Corrêa; da Câmara, Luís Fernando; Hahn, Lisiane
Abstract: Free‐flowing tributaries are important for the maintenance of fish diversity in dammed systems. In relation to the reproduction of fish species, the role of a free‐flowing tributary was evaluated and compared with that of a dammed tributary downstream of large dams in the Madeira River, one of the main tributaries of the Amazon River. Two hypotheses were tested: (i) the densities of the ichthyoplankton differ between the dammed and the free‐flowing tributaries; and (ii) the free‐flowing tributary contributes a greater diversity of fish larvae species to the assemblage structure of the main stem than the dammed tributary. Fish eggs and larvae were sampled at five sites: one in each tributary (Jamari – dammed – and Machado – free‐flowing) and three in the main stem (Madeira River), upstream and downstream from the mouth of each tributary. Fitted Bayesian models showed that the densities both of eggs and larvae were more than twice as high in the free‐flowing tributary than in the dammed tributary. The results also indicated that the free‐flowing tributary makes a major contribution to the fish assemblage structure of the Madeira River, whereas the dammed tributary does not have a significant influence on the main stem assemblage structure. The results demonstrate the importance of conservation and maintenance not only of the Machado River but also of other free‐flowing tributaries in dammed basins, especially those basins with high biodiversity, such as the Amazon. Moreover, this study helps inform the decision‐making process regarding the location of new dams, which is critical in fish diversity conservation.